2016
DOI: 10.1152/ajpregu.00212.2016
|View full text |Cite
|
Sign up to set email alerts
|

Dietary thylakoids reduce visceral fat mass and increase expression of genes involved in intestinal fatty acid oxidation in high-fat fed rats

Abstract: Thylakoids reduce body weight gain and body fat accumulation in rodents. This study investigated whether an enhanced oxidation of dietary fat-derived fatty acids in the intestine contributes to the thylakoid effects. Male Sprague-Dawley rats were fed a high-fat diet with (n = 8) or without thylakoids (n = 8) for 2 wk. Body weight, food intake, and body fat were measured, and intestinal mucosa was collected and analyzed. Quantitative real-time PCR was used to measure gene expression levels of key enzymes involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…We however found no sign of steatorrhea in spite of a body weight loss, neither in rodent studies [7] nor in human studies [8, 9]. We also observed an increased expression of fat oxidative enzymes in the gut and an increased fat oxidation in rat fed high-fat diet with thylakoid supplementation [10], suggesting other mechanisms to explain the fat mass reduction. This could be fecal fat excretion and/or a recruitment of new adipocytes that have a more active metabolism.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…We however found no sign of steatorrhea in spite of a body weight loss, neither in rodent studies [7] nor in human studies [8, 9]. We also observed an increased expression of fat oxidative enzymes in the gut and an increased fat oxidation in rat fed high-fat diet with thylakoid supplementation [10], suggesting other mechanisms to explain the fat mass reduction. This could be fecal fat excretion and/or a recruitment of new adipocytes that have a more active metabolism.…”
Section: Introductionmentioning
confidence: 67%
“…The thylakoid enriched high-fat diet used in mice was the same as previously used for rat, suggesting a species difference. In rat, the absence of fat in faeces could be due to a slower passage of food through the intestine [9], giving the possibility for an increased intestinal fatty acid oxidation [10] and/or a more complete fat absorption.…”
Section: Discussionmentioning
confidence: 99%
“…. Thylakoids appear to specifically and efficiently inhibit eating in humans and animals. This effect appears to be related to a stimulation of the secretion of satiating gut peptides, such as CCK and glucagon-like peptide 1 (GLP-1) , and, possibly, to a stimulation of the oxidation of dietary-derived fatty acids in the small intestine . Interestingly, in humans, thylakoids appear to have a particularly strong inhibitory effect on hedonic eating, i.e., on the overeating when exposed to good-tasting, attractive food .…”
Section: Thylakoidsmentioning
confidence: 99%
“…The gut microbiota also promotes the production of SCFA, which have been proposed to have effects on lipid, glucose and cholesterol metabolism in the host [ 33 , 34 ]. Indeed, a recent study in rats fed a high-fat diet with or without thylakoids demonstrated that thylakoid supplementation resulted in a reduced respiratory quotient (RQ), indicative of increased fatty acid oxidation [ 35 ]. This may have been caused by altered gut microbiota.…”
Section: Discussionmentioning
confidence: 99%